Percutaneous Vertebroplasty for Painful Compression Fractures in a Small Cohort of Patients with a Decreased Expectation-Related Placebo Effect due to Dementia - Lehman, V.T.; Gray, L.A.; Kallmes, D.F. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Although abundant literature has reported success with vertebroplasty for the treatment of painful compression fractures, none has accounted for a potential expectation-related placebo effect. We report the results of vertebroplasty for painful vertebral body compression fractures in a small cohort of patients with dementia with the assumption that this patient subgroup is subjected to a decreased placebo effect.MATERIALS AND METHODS: All patients with objective evidence of dementia (N = 10) who had undergone vertebroplasty at our institution were identified from a comprehensive prospectively constructed vertebroplasty data base. The patients’ pain at rest and activity, mobility, and pain-medication use were analyzed at 2 hours postprocedure, 1 week, 1 month, 6 months, and 1 year.RESULTS: Pain with activity decreased or resolved in 80%–100% of patients at each time point, whereas pain at rest decreased or resolved in 78%–100% of all patients at each time point. Improved mobility was reported in 80%–100% of patients at all time points. Pain medication was decreased or stopped in 67% of patients at 1 week and in 100% of patients at 6 months and 1 year.CONCLUSION: Treatment of painful compression fractures in patients with dementia demonstrates a high rate of success regarding pain relief and mobility. This study offers additional evidence that vertebroplasty has true benefit.